Policy Transfer Through Return Migration: Lesson From Indonesian Returnees - Violita Sinda Arinda; Reza Fathurrahman (Magister Ilmu Administrasi Publik, 2021)
This article investigates the extent to which policy transfer activities facilitated by Indonesian skilled returnees after finishing their studies in Germany can support various local actors in accelerating developmental progress in their homeland. By using the five-dimensional policy transfer (Evans, 2017), this study found that returnees strengthen the working environment by promoting exchange of knowledge, improving current work methods, and advocating for most common forms of transfer including knowledge sharing, experiences, and networks that they had while abroad. The research also found that most cases of successful policy transfer adoption were characterized by hybridization of new ideas with existing policy and institutional framework in organizations that participated in the program.